QTL ANALYSIS OF BIOCHEMICAL TRAITS OF QUALITY IN BRASSICA RAPA L. - A. M. Artemyeva; A. E. Solovieva; N. V. Kocherina; Yu. V. Chesnokov (Овощи России)
Using two mapping populations of DH lines of Brassica rapa (DH30, obtained by crossing of turnip and yellow sarson, and DH38, obtained by crossing of pakchoi and yellow sarson) the QTL analysis of five biochemical traits of quality was done. For the first time in Russia, for each investigated trait was determined QTL, as well as the effects of action of reviled QTL, percent of phenotype variability for each QTL and molecular markers genetically linked with identified QTL. Reviled molecular markers can be used as effective tool upon mass screening of collection and breeding material for biochemical traits of quality.